Efficacy of Different Solvents in the Extraction of Bioactive Compounds and Anticancer Activities of Thyme (Thymus vulgaris L.) Leaves and Twigs - Kamalia, Aify Zulfa; Tunjung, Woro Anindito Sri (Indonesian Journal of Pharmacy, 2023)
Thyme contains phytochemicals that exhibit cytotoxic and cytogenic activities. Differ solvents have different abilities in dissolving plant bioactive compounds. The objective of this study is to determine the anticancer properties of thyme leaves and twigs including profile of bioactive compounds, cytotoxicity, ability of apoptosis induction and caspase-3 activation of different solvent extracts on T47D breast cancer cell line. An experimental study was conducted in eight groups. T47D breast cancer cell line was treated with thyme extracts as treatment group, doxorubicin as positive control, while untreated T47D cells were used as negative control. Thyme was extracted by maceration using 6 different solvents: methanol, ethanol, chloroform, ethyl acetate, dichloromethane, and n-hexane. Bioactive compounds of all extracts were analyzed by GC-MS. Cytotoxicity was investigated through MTT assay on T47D breast cancer cell line. The percentage of apoptosis and caspase-3 were detected by flow cytometry using Annexin V-PI and BD Cytofix/Cytoperm, respectively. Thymol as the main bioactive compound in thyme was found in all extracts. MTT results revealed that six solvents extracts had moderate to weak cytotoxicity with dichloromethane had the lowest IC50 values at 120.23 µg/ml. All thyme extracts promoted apoptosis in T47D cells with apoptosis percentage of methanol, chloroform, ethyl acetate, ethanol, dichlorometane, n-Hexane and doxorubicin were 82.67; 80.98; 73.13; 72.28; 60.62; 27.74 and 98.43%, respectively. Among all extracts, methanol extract showed the highest apoptosis and caspase-3 activation percentage. We conclude that all thyme extracts had anticancer properties in T47D breast cancer cell line although efficacy of each solvent extract was differed.